Evaluación y validación de los monitores Omron Hem 705 CP y Hem 706/711 para automedidas de presión arterial - Artigao, L.M. (Aten Primaria, 2000)
OBJETIVE: To validate two devices for self-measurement of blood presure –The Omron Hem- 705CP and the Omron Hem 706/711– according to the revised protocol of the British Hypertension Society (BHS).The results were also analysed according to the criteria for accuracy of the revised standard of the Association for the Advancement of Medical Instrumentation (AAMI). DESIGN: The British Hypertension protocol for the evaluation of blood presure measuring devices. SETTING: Primare care. Zone III Health Care in Albacete (Spain). PARTICIPANTS: 95 subjets to validate the Omron 706/711 and 100 subjets to Omron 705. RESULTS: Two monitors surpassed the validation according to the standars set out by the BHS protocol (705 with a A grading for SBP and DBP, 706/711 obtained a B grading for SBP and an A grading for DBP and a PASS for SBP and DBP. Upon analyzing the behavior of the appliances by subgroups of BP measures (high, mid, and low), 705 for SBP > 160 mmHg obtained a B grading for the BHS protocol, but it did not pass the accuracy AAMI criteria (SD, 8.5, but difference between observers-device is –0,1 mmHg). The rest of subgroups of BP obtained a A grading for the BHS protocol and a PASS (AAMI). 706/711 surpassed in all BP subgroups BHS protocol, for DBP 80-100, SBP > 160 and DBP > 100 with a B grading, for the rest of BP subgroups obtained a B grading and a PASS (AAMI). CONCLUSIONS: On the basis of these results, we conclude both monitors Omron HEM 706/711 and the Omron 705CP surpassed the accuracy criteria required for BHS and AAMI, and can be recommended for clinical use.